The rise of the civilizational state - Coker, Christopher (Polity Press, 2019)
"In this pioneering book renowned political philosopher Christopher Coker looks in-depth at two countries that now claim this title: Xi Jinping's China and Vladimir Putin's Russia. He also discusses the Islamic caliphate, a virtual and aspirational civilizational state that is unlikely to fade despite the recent setbacks suffered by ISIS. The civilizational state, he contends, is an idea whose time has come" -- Provided by publisher.